2023
DOI: 10.1038/s41421-022-00506-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cellular evolution of the amygdala across species analyzed by single-nucleus transcriptome profiling

Abstract: The amygdala, or an amygdala-like structure, is found in the brains of all vertebrates and plays a critical role in survival and reproduction. However, the cellular architecture of the amygdala and how it has evolved remain elusive. Here, we generated single-nucleus RNA-sequencing data for more than 200,000 cells in the amygdala of humans, macaques, mice, and chickens. Abundant neuronal cell types from different amygdala subnuclei were identified in all datasets. Cross-species analysis revealed that inhibitory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 100 publications
4
24
0
Order By: Relevance
“…Although LAMP5 protein is localized in axon terminals of GABAergic neurons 87 , our smFISH data shows LAMP5 transcripts localized in cell bodies. Interestingly, LAMP5 + excitatory neurons are found in human samples in cortical layer 2/3 and in the basolateral amygdala, and both inhibitory and excitatory LAMP5 + cells are more abundant in humans than mice 88,89 . Additional research is needed to determine if the increase in LAMP5 over age is due to increased LAMP5 transcription in expressor cells, recruitment of previously non-expressing cells to the LAMP5+ population, or proliferation of a LAMP5 + population.…”
Section: Discussionmentioning
confidence: 99%
“…Although LAMP5 protein is localized in axon terminals of GABAergic neurons 87 , our smFISH data shows LAMP5 transcripts localized in cell bodies. Interestingly, LAMP5 + excitatory neurons are found in human samples in cortical layer 2/3 and in the basolateral amygdala, and both inhibitory and excitatory LAMP5 + cells are more abundant in humans than mice 88,89 . Additional research is needed to determine if the increase in LAMP5 over age is due to increased LAMP5 transcription in expressor cells, recruitment of previously non-expressing cells to the LAMP5+ population, or proliferation of a LAMP5 + population.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, eight clusters were enriched for inhibitory GABAergic markers, which showed a great diversity of classes and subclasses, some with clinical relevance in psychiatric disease and addiction behaviors (Tran et al., 2021). Single‐nucleus transcriptomic study of a higher number of human CeA cells from three postmortem samples revealed more clusters with a complex local cellular composition of excitatory neurons that are evolutionarily more diverse than the abundant quantity of inhibitory neurons (Yu et al., 2023). In other study with three postmortem male donors, the CeA displayed interneuron clusters from different embryonic origins, a relatively specific excitatory cells cluster, as well as superclusters named deep‐layer intratelencephalic‐projecting, deep‐layer corticothalamic‐projecting, medium spiny neurons (MSN) and eccentric MSN, and a “splatter” one (i.e., a “miscellaneous” supercluster containing rare neuronal cell types; see “CEN” data in figure 2A from Siletti et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…FA trajectories showed some increases during development for 4/5 structures (except amygdala) in line with what is seen for white matter tracts, albeit by a lot less, but the subsequent decrease with aging to yield an inverted U trajectory was only observable for globus pallidus and hippocampus. The amygdala showing a steady linear decrease in FA, but given the myriad of cells composing this structure (Yu et al, 2023) a physiological cause of such a trajectory is unclear. In contrast, the FA of the striatum increased with age over the entire lifespan in both cohorts, in agreement with other aging studies reporting linear increases in FA for the putamen (part of the striatum)(Abe et al, 2008; Pal et al, 2011; Wang et al, 2010), but an observation not seen in WM (Lebel et al, 2012).…”
Section: Discussionmentioning
confidence: 99%